1993
DOI: 10.2105/ajph.83.2.270
|View full text |Cite
|
Sign up to set email alerts
|

The nitrate contamination of private well water in Iowa.

Abstract: The State-Wide Rural Well-Water Survey was conducted between April 1988 and June 1989. About 18% of Iowa's private, rural drinking-water wells contain nitrate above the recommended health advisory level (levels of NO3-N greater than 10 mg/L); 37% of the wells have levels greater than 3 mg/L, typically considered indicative of anthropogenic pollution. Thirty-five percent of wells less than 15 m deep exceed the health advisory level, and the mean concentration of nitrate-nitrogen for these wells exceeds 10 mg/L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
4
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 12 publications
1
83
4
4
Order By: Relevance
“…These well features were associated with elevated nitrate levels in our water samples, a finding which is consistent with findings of other studies that have shown that well depth, diameter, age, and construction type are important indicators of well water contamination (Johnson and Kross, 1990;Kross et al, 1993;US EPA, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…These well features were associated with elevated nitrate levels in our water samples, a finding which is consistent with findings of other studies that have shown that well depth, diameter, age, and construction type are important indicators of well water contamination (Johnson and Kross, 1990;Kross et al, 1993;US EPA, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…Concern with health effects of nitrates consumed in drinking water is far from being totally eliminated in the US. In fact, a startling number of wells throughout the US farm belt have water containing nitrate that exceeds the US Environmental Protection Agency limit of 10 mg /l nitrate -nitogen ( Johnson and Kross, 1990;Kross et al, 1993 ). Of wells in South Dakota, which were not drilled to over 40 m deep, 39% contained nitrate levels that exceeded the EPA limits (Johnson and Kross, 1990 ).…”
Section: Nitrate Exposure In Transylvaniamentioning
confidence: 99%
“…Gaseous nitrogen can be found in many forms such as N 2 , N 2 O, NO, NO 2 , NH 3 and NH 4 (Comly, 1987;Kross et al, 1993). Although there are many sources of nitrogen (both natural and anthropogenic) that could potentially lead to the pollution of groundwater with nitrates, the anthropogenic sources are really the ones that most often cause the amount of nitrate to rise to a dangerous level (Hallberg & Keeney, 1993).…”
Section: Introductionmentioning
confidence: 99%